Anti-A and Anti-B Haemolysins amongst Group "O" Voluntary Blood Donors in Northeastern Nigeria. (3rd October 2010) - Kagu, M. B.; Ahmed, Sagir G.; Mohammed, Aisha A.; Moshood, Waheed K.; Malah, Mohammed B.; Kehinde, Jimoh M.
Abstract : Background and Objective . The aim of this study was to determine the prevalence and haemolytic significance of alpha- and beta-haemolysins in our voluntary group "O" donor population. Methods . This was a prospective study carried out at North-East Zonal Centre, the National Blood Transfusion Service, Maiduguri, Nigeria from April 2007 to April 2009. One thousand nine hundred and twenty nine voluntary group "O" blood donors (1609 males and 320 females, median age 26 years± 7.6 SD) were screened for alpha- (anti-A) and beta- (anti-B) haemolysins using the standard tube technique at 37 degrees C for 1 hour. All samples showing haemolysis were titrated for anti-A and anti-B haemolysins. Results . The overall prevalence of haemolysins in group O donors was 55.4%. Prevalence of alpha- and beta-haemolysins only was 10.3% and 12.6%, respectively, while that of donors having both alpha- and beta-haemolysins in their sera was 32.5%. Visual titre of 8 was seen in 0.4% of lytic alpha-haemolysin and 0.2% of lytic beta-haemolysin whereas donors with both alpha- and beta-haemolysins had a titre of 1.8%. Lytic titre of 16 and 32 was very low in our donor population. Conclusion . This study has shown that although the prevalence of haemolysins is high in our voluntary group "O" donor population, the strength of the lytic antibodies is low. Therefore, despite the labour intensiveness of our haemolysis titration technique and the frequent transfusion of group O blood to certain recipients of blood group A, B, and AB in our environments, there is the need to routinely screen our donors for haemolysins in order to identify those posing the greatest risk to recipients. Further studies to determine episodes of clinically significant haemolysis in recipients of blood group O may be necessary.